An application example of the likelihood ratio approach to the evaluation of organic gunshot residues using a fictional scenario and recently published data. (June 2022) - Maitre, Matthieu; Horder, Mark; Kirkbride, K. Paul; Gassner, Anne-Laure; Weyermann, Céline; Gupta, Anjali; Beavis, Alison; Roux, Claude
Abstract: The analysis of gunshot residues (GSR) can provide important information with regard to the involvement of a person of interest (POI) in a firearm-related incident. Organic gunshot residues (OGSR) have been investigated in order to provide additional and complementary information to the traditional inorganic gunshot residue (IGSR) particles detected by scanning electron microscopy (SEM). Currently, many procedures and analytical methods have been developed to detect OGSR-related compounds collected from the shooter's hands. However, such studies provide no information regarding the inclusion of such results in an activity level evaluation for discharging a firearm. The aim of this article is to assess the feasibility of using the likelihood ratio (LR) approach as a tool to evaluate OGSR results for activity level propositions. The developed model focuses on the assignment of an LR for several compounds detected in OGSR. A simple worst-case simulation was investigated in order to assess the applicability of the LR approach to evaluate OGSR traces. This simulation highlighted the importance of addressing an appropriate pair of activity level propositions when evaluating the results. Highlights: An LR approach for the evaluation of organic gunshot residues (OGSR) is discussed. The approach focuses on diphenylamine, ethylcentralite and N-nitrosodiphenylamine. The LR is calculated following a normal density function. The LR approach is applied to OGSR results for activity level propositions. A simple worse case simulation is presented as a proof of concept.